Design and Development of Mach Zehnder Interferometer based Optical Sensors to Detection of Arsenic compound in Drinking Water - Afzal Nehal, Shaikh; Mukherjee, Anindita; Manju Devi, Dr. (International Journal of Engineering and Technology, 2018)
Water, the inevitable need of any individual, must be monitored. Detection of the arsenic chemicalÂ present in water leads to contagious diseases. The legacy makes people difficult to survive. The consequences are cancer, other diseases.Â Employing photonic crystal waveguide with the rally round of mach Zehnder interferometer, it is feasible to correctly compute arsenic compound level in water.Â Â MZI sensor has many compensation, diminutive, least use of instrumentation, and ready to be used with CMOS technology. Follows in the paper, arsenic compound level of wavelength range of 1530â€“1565 nm is analyzed and detected. Experiential program from the band arrangement that for minute change in refractive index is accounted, subsequently logical shift in the frequency and amplitude will be evident enlarging mach Zehnder interferometer will behave as a sensor. Thus projected alternate included optical Mach Zehnder Interferometer (MZI), composed ofÂ graded index channel waveguide that can be frequently used as chemical and biological sensor in this manuscript. This dissertation describes how the MZI operates two arms predominantly to conquer the industrial challenges. Manuscript represents test data, graph and results that exemplify the performance of whole system.Â